Geomorphology of the topmost part of the Bistra Mountain, Mavrovo Park, North Macedonia. Issue 2 (1st December 2021) - Isola, I.; Ribolini, A.; Bini, M.; Zanchetta, G.; Milevski, I.
ABSTRACT: Identification of the remnant traces of paleo-glaciers provides important proxies to understand the response of the environment to rapid climate changes. We present a 1:25, 000 scale geomorphological map covering ∼12.5 km 2 of the upper part of Mount Bistra (North Macedonia) on the basis of remote sensing analyses and geomorphological surveys. Particular attention is given to the description of glacial and periglacial landforms, to the reconstruction of single glacier shapes and to Equilibrium Line Altitude (ELA) value calculation. The results of the survey and the reconstructed ELAs indicate the occurrence of three glacial phases that led to the formation of frontal and lateral moraines. The age of these phases is tentatively attributed to the Late Pleistocene by comparing these ELAs with those of other Balkan mountains. This map is the first step of a wider project aimed at reconstructing the relation between climate change and geomorphic response in this area.